Antiobesity Effect of NADES (Natural Deep Eutectic Solvent) Extract of Purslane Herb (Portulaca oleracea L.) on Male Rats (Rattus norvegicus) - Azizah, Rizqi Nur; Santi, Irma; Awali, Muhammad Noer; Putra, Bayu; , Faradiba (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: Obesity is a metabolic disorder characterized by excessive fat accumulation, leading to various health complications. One potential approach to managing obesity is through natural products, such as medicinal plants. Aims: This study evaluates the anti-obesity activity of purslane (Portulaca oleracea L.) extract obtained using the green extraction method in male rats (Rattus norvegicus). Method: A total of 18 male rats were divided into six groups: normal control, negative control (Na-CMC + NADES), positive control (orlistat), and three treatment groups receiving NADES Purslane Herb Extract (NPHE) at doses of 50, 100, and 200 mg/kg BW. The treatment groups were induced with a high-fat diet for 30 days, followed by 14 days of therapy. Result: Statistical analysis using One-Way ANOVA and Bonferroni post-hoc test showed that NADES purslane herb extract exhibited significant anti-obesity effects, with the most effective dose being 200 mg/kg BW, which reduced body weight by 13.004% and BMI by 17.935% in male rats. Conclusion: These findings suggest that purslane extract has potential as a natural anti-obesity agent. Further research is needed to explore its bioactive compounds and mechanisms of action, supporting its potential development in pharmaceutical and nutraceutical applications.